Involvement of Children with Special Needs in Learning in Inclusive Schools - Ady Dharma, Dwitya Sobat; Hermanto, Hermanto (Journal of ICSAR, 2020)
Children with Special Needs who process in Inclusive Education Organizing Schools (SPPI) often seem left out not to develop their best potential, are shackled with labels, and marginalized socially and academically. This negative impression can be minimized by increasing the involvement of children with special needs in learning. However, many schools still do not know the level of involvement of children with special needs in SPPI. This study aims to determine the level of involvement of children with special needs in learning by using an intrinsic case study approach to nine children with special needs with a variety of mental retardation, autistic, slow learner, disabled and low vision in semester 1 of 2018/2019 academic year at an SPPI. This article describes the level of student involvement in terms of cognitive, emotional, and behavioral aspects. The results showed that the level of involvement of children with special needs varied greatly depending on cognitive abilities and the environment's role in creating creative learning.